Sistem Informasi Akuntansi BMD Terhadap Pengelolaan Asset Daerah Pada DPPKAD Kota Gorontalo - Irawati Pangat; Tri Handayani Amaliah; Lukman Pakaya (Jambura Accounting Review, 2020)
The purpose of this study was to determine the effect of regional accounting information systems on regional asset management. The method used in this study uses quantitative methods using simple regression analysis. The results in this study are the Regional Accounting Information System influences the Regional Asset Management. The independent variable studied had a contribution of 70.1% to the Regional Asset Management variable, while the other 29.9% was influenced by other factors outside the variable under study.